The success of the tumor immunotherapy: neutrophils from bench to beside - Meng Zhu; Ru Jia; Xiaojie Zhang; Pingwei Xu (Frontiers in Immunology)
The present immune therapy was focused on the immune checkpoint blockade or Chimeric Antigen Receptor T-Cell Immunotherapy (CART) transfer, but how to activate the innate immune system to antitumor still lags out. Neutrophils are the most abundant circulating leukocytes in human, and heterogeneous neutrophils have been increasingly recognized as important players in tumor progression. They play double “edge-sward” by either supporting or suppressing the tumor growth, including driving angiogenesis, extracellular matrix remodeling to promote tumor growth, participating in antitumor adaptive immunity, or killing tumor cells directly to inhibit the tumor growth. The complex role of neutrophils in various tumors depends on the tumor microenvironment (TME) they are located, and emerging evidence has suggested that neutrophils may determine the success of tumor immunotherapy in the context of the immune checkpoint blockade, innate immune training, or drug-loaded extracellular microvesicles therapy, which makes them become an exciting target for tumor immunotherapy, but still with challenges. Here, we summarize the latest insights on how to activate neutrophils in antitumor immunity and discuss the advances of neutrophil-targeted immunotherapy strategies.